GENETIC STUDIES OF RELATIONSHIP BETWEEN PENAEUS SEMESULACATUS, PENAEUS JAPANICUS AND META PENAEUS MONOCEROS USING BIOCHEMICAL AND MOLECULAR TOOLS: Life Sciences-Biotechnology - AHMED M. DARWISH; MOHSEN S. H; ABDELGHANY M. F; FAGR KH. ABDEL-GAWAD; WAGDY K. B. KHALIL (International Journal of Life Science and Pharma Research, 2022)
A comparative study of three shrimp populations (Penaeus semesulacatus, Penaeus japonicus, Meta penaeus monoceros) was carried out. Biochemical and the molecular genetic structure of the relevant population was investigated using SDS- PAGE, RAPD and ISSR Techniques. A high degree of similarity was detected by SDS-PAGE within each population and the similarity values were equal to 0.87 when calculated in .semesulacatus population, o.9 in P. Japonicus population and o.85 in M. P. Monoceros population. The data inferred from molecular markers obtained by ISSR and RAPD–PCR were used to calculate the genetic distances, and showed that M.P. Monoceros was distantly related from P.japonicus and P.semesulacatu. Also, the P.semesulacatus and P.japonicus had relatively high level of genetic relationship. The present study revealed that the ISSR and RAPD Techniques are powerful tools in detecting genetic variations.